Gelatin-methacryloyl hydrogel based in vitro blood–brain barrier model for studying breast cancer-associated brain metastasis. (21st April 2021) - Augustine, Robin; Zahid, Alap Ali; Mraiche, Fatima; Alam, Khurshid; Al Moustafa, Ala-Eddin; Hasan, Anwarul
Abstract: Breast cancer is one of the leading causes of brain metastasis. Metastasis to the brain occurs if cancer cells manage to traverse the 'blood-brain barrier' (BBB), which is a barrier with a very tight junction (TJ) of endothelial cells between blood circulation and brain tissue. It is highly important to develop novel in vitro BBB models to investigate breast cancer metastasis to the brain to facilitate the screening of chemotherapeutic agents against it. We herein report the development of gelatin methacryloyl (GelMA) modified transwell insert based BBB model composed of endothelial and astrocyte cell layers for testing the efficacy of anti-metastatic agents against breast cancer metastasis to the brain. We characterized the developed model for the morphology and in vitro breast cancer cell migration. Furthermore, we investigated the effect of cisplatin, a widely used chemotherapeutic agent, on the migration of metastatic breast cancer cells using the model. Our results showed that breast cancer cells migrate across the developed BBB model. Cisplatin treatment inhibited the migration of cancer cells across the model. Findings of this study suggest that our BBB model can be used as a suitable tool to investigate breast cancer-associated brain metastasis and to identify suitable therapeutic agents against this. Graphical Abstract: UF0001